2009
DOI: 10.1534/genetics.108.096149
|View full text |Cite
|
Sign up to set email alerts
|

TheSaccharomyces cerevisiae PRM1Homolog inNeurospora crassaIs Involved in Vegetative and Sexual Cell Fusion Events but Also Has Postfertilization Functions

Abstract: Cell-cell fusion is essential for a variety of developmental steps in many eukaryotic organisms, during both fertilization and vegetative cell growth. Although the molecular mechanisms associated with intracellular membrane fusion are well characterized, the molecular mechanisms of plasma membrane merger between cells are poorly understood. In the filamentous fungus Neurospora crassa, cell fusion events occur during both vegetative and sexual stages of its life cycle, thus making it an attractive model for stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 51 publications
3
85
0
1
Order By: Relevance
“…Out of the 96% of mutant prezygotes, an 85% exhibited fluorescence in half of the zygote body (see cell a in Figure 2B), while 11% of the prezygotes exhibited fluorescence in more or in less than half of the zygote body (see cells b-d in Figure 2B; see also Supporting Information, Figure S1). This observation suggested that intercellular bubbles/fingers, like those described for the S. cerevisiae and N. crassa prm1D mutants (Heiman and Walter 2000;Fleissner et al 2009), had been produced.…”
Section: Prm1 + Is Required For Cell Fusionmentioning
confidence: 53%
See 4 more Smart Citations
“…Out of the 96% of mutant prezygotes, an 85% exhibited fluorescence in half of the zygote body (see cell a in Figure 2B), while 11% of the prezygotes exhibited fluorescence in more or in less than half of the zygote body (see cells b-d in Figure 2B; see also Supporting Information, Figure S1). This observation suggested that intercellular bubbles/fingers, like those described for the S. cerevisiae and N. crassa prm1D mutants (Heiman and Walter 2000;Fleissner et al 2009), had been produced.…”
Section: Prm1 + Is Required For Cell Fusionmentioning
confidence: 53%
“…Out of the 96% of mutant prezygotes, an 85% exhibited fluorescence in half of the zygote body (see cell a in Figure 2B), while 11% of the prezygotes exhibited fluorescence in more or in less than half of the zygote body (see cells b-d in Figure 2B; see also Supporting Information, Figure S1). This observation suggested that intercellular bubbles/fingers, like those described for the S. cerevisiae and N. crassa prm1D mutants (Heiman and Walter 2000;Fleissner et al 2009), had been produced.The distribution of cell wall and plasma membrane at the cell-cell contact area of prm1D zygotes is abnormal When the mating process was analyzed in strains bearing fluorescent membrane and nuclei markers (Figure 2A), it was found that most of the control and prm1D prezygotes exhibited a flat plasma membrane separating the mating partners (an example is denoted by an arrow in Figure 3A). However, in the mutant strain a significant number of prezygotes exhibited an accumulation of membranous material (denoted by arrowheads in Figure 3A), membrane bubbles/fingers (asterisks in Figure 3A), and cell compartments delimited by two membranes (denoted by a cross) that were sometimes accompanied by a bubble.…”
mentioning
confidence: 53%
See 3 more Smart Citations